A new synthetic protocol for coumarin amino acid - Xu, Xinyi; Hu, Xiaosong; Wang, Jiangyun (Beilstein Journal of Organic Chemistry, 2013)
The hydrochloride of the racemic amino acid (2-(7-hydroxycoumarin-4-yl)ethyl)glycine, which can serve as a fluorescent probe in proteins, and two halogen derivatives of it, were synthesized by using a new synthetic protocol in five steps. It is less costly and relatively easy to prepare this kind of fluorescent amino acid with the new synthetic method. Furthermore, it can be applied to synthesize other derivatives of the coumarin amino acid with some specific properties.
Keywords: coumarin; fluorescent probe; halogen derivatives; non-natural amino acid; Pechmann condensation